The role of housing design in a multiple fans system with a piezoelectric actuator. (5th December 2015) - Ma, H.K.; Li, Y.T.; Ke, S.Y.; Lin, C.P.
Abstract: A multiple fans with piezoelectric actuator system (MFPA) that combines piezoelectric effect, magnetic effect and resonance effect to drive passive fans vibrating simultaneously offers better thermal performance than a single piezoelectric fan as proposed in previous studies. In this study, a modular MFPA with a housing designed to concentrate airflow was developed and its thermal performance was investigated. Dimensionless heat convection number ( M MFPA ) was defined to compare the thermal performance of the ar MFPA with natural convection. The results indicated that the geometry of the housing can significantly influence the thermal performance of the modular MFPA. The airflow generated from the MFPA was concentrated when Z ∗ decreased from 2.5 to 1.25 at Y ∗ = 0.917 and θ = 0°; the results showed T ∗ ( t ) decreased from 0.76 to 0.67. Moreover, under the case of Z ∗ = 1.25 and θ = 0°, T ∗ ( t ) further decreased from 0.67 to 0.60 when Y ∗ decreased from 0.917 to 0.417. To optimize the thermal performance of the modular MFPA, a nozzle was applied for concentrating airflow. The results showed an optimal value of M MFPA of 2.57 when the nozzle angle ( θ ) was 63.43° under the case of Z ∗ = 1.25, Y ∗ = 0.417. Highlights: A housing design was applied to a multiple fans system with a piezoelectric actuator (MFPA). Effects of the housing geometries including height, width and nozzle angle of the housing are discussed. Compared to natural convection, the thermal performance of the system can be improved by 2.57 times.